TRAINING ON LEARNING TRILINGUAL VOCABULARY WITH BRAILLE TRINGUAL LANGUAGE MODULE AT MTS LB/A YAKETUNIS YOGYAKARTA - Syafira Intan Muhliana; Yosi Wulandari; Tsulusiyah Apriliyananingrum; Nenden Wulan Septianning Tiyas; Nurul Fitrah Amaliah Suharsono (Universitas PGRI Sumatera Barat, 2023)
MTs LB/A Yaketunis Yogyakarta is an inclusive educational institution specifically for blind people who have an excellent program for memorizing the Qur'an. MTs LB/A has limited teaching materials that support the success of teaching and learning. One of the obstacles in the learning process is the low mastery of student vocabulary, especially in Indonesian, English, and Arabic learning so that it has an impact on student learning outcomes. This is because there are no braille learning books that support the learning process. The objectives of this activity are (1) providing training on increasing trilingual vocabulary, namely Indonesian, English, and Arabic in fulfilling aspects of reading, writing, speaking, and vocabulary for MTs LB/A Yaketunis Yogyakarta students; (2) Creation and application of optimal learning resources for blind students through learning modules. The methods of this activity are (a) determination of partners, conducting surveys and discourses, (c) licensing, (d) material development, module preparation, making Trilingual Language modules, Braille Trilingual Language development program manuals, Braille Games (Puzzle Beam and Braille Flashcard, (e) conducting pretests, implementing modules and games, implementing postes, (f) program evaluation. The result of this training activity is an increase in students' ability to master vocabulary Indonesian 27%, English 28%, and Arabic 37%. The realization of learning materials for Braille Trilingual Language and Braille Games modules can improve students' knowledge and skills in learning three languages.